Peranan Kepemimpinan Tolotang Benteng dalam Pemerintahan yang Baik di Kelurahan Amparita Kecamatan Tellu LimpoE Kabupaten Sidenreng Rappang - Emelia Syahruddin (PRAJA: Jurnal Ilmiah Pemerintahan, 2019)
Abstract This research was conducted Amparita Sub-district of Tellu LimpoE District in Sidenreng Rappang Regency, arguing the Tolotang Benteng Leadership in the area was still very respected and influential in the order of society so as to appeal a study, done by the authors. The goal was to identify and study the role of traditional leadership in Tolotang Benteng in term of good governance. Data collection methods used in this study were the technique of observation / direct observations, questionnaires, interviews, and library research. The data analysis technique used was qualitative data analysis techniques, in which the author described the overall data and then drew conclusions using percentage frequency tables. The population in this study took all Tolotang Benteng people while sampling technique used was purposive sampling. The role of Tolotang Benteng Leadership was very influential in its community, specifically included social control, role model, motivator, and the main pillar in preservation and development of local wisdom, culture and socialize policies and good governance programs. The role of Tolotang Benteng Leadership as social control in good governance scored 70% as instrumental. The disseminating of policies and good governance showed only 50% of respondents stated very influential. As role models and motivators were as much as 80% or 40 respondents stated a very important role. In addition, as the main pillar in preservation and development of local wisdom and culture in good governance was 70% indicated instrumental. The above results were supported by the affecting factors, such as the quality of Tolotang Benteng leader, a good relationship between traditional leaders and the government, and community participation in the area itself.